2007
DOI: 10.1016/j.immuni.2007.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Entry Route of Salmonella typhimurium Directs the Type of Induced Immune Response

Abstract: Secretory immunoglobulin A (SIgA) represents a first line of defense against mucosal pathogens by limiting their entrance. By using different strains of Salmonella typhimurium that target the two mechanisms of bacterial entry (microfold cell [M cell]- or dendritic cell-mediated), we demonstrated here that the distribution of bacteria after oral infection directed the type of induced immune response. M cell-penetrating invasive, but not noninvasive, S. typhimurium was found in large numbers in Peyer's patches (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(120 citation statements)
references
References 47 publications
5
113
1
1
Order By: Relevance
“…Therefore, the exclusive role of PP for the induction of IgA has been a matter of debate for a long time. Recent observations indicate that PP appear to be essential for intestinal immune responses to Salmonella (45)(46)(47), even though conflicting results have been obtained regarding the role of SILT in anti-Salmonella responses (48).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the exclusive role of PP for the induction of IgA has been a matter of debate for a long time. Recent observations indicate that PP appear to be essential for intestinal immune responses to Salmonella (45)(46)(47), even though conflicting results have been obtained regarding the role of SILT in anti-Salmonella responses (48).…”
Section: Discussionmentioning
confidence: 99%
“…As in the case of PPs, a follicle associated epithelium with M cells is present on the lumen facing side of ILFs. Uptake of pathogens including S. typhimurium, leads to the formation of germinal centers (GCs) in mature ILFs [64][65][66]. Interestingly, it was found that the presence or absence of GCs in ILFs did not influence the active class switching of naïve B cells to active IgA secreting B cells [67].…”
Section: Antigen Uptake In the Gutmentioning
confidence: 99%
“…This in turn promotes bacterial escape into the subepithelial compartment (36) and dissemination of the bacteria both locally and systemically. Surprisingly, the SPI-1-dependent pathway of invasion appears to be less important, because SPI-1-deficient Salmonellae still infect mice and cause colitis (34), although mucosal IgA responses are reduced (37). This observation raises the question as to what the biological relevance of the SPI-1-dependent invasion pathway might be.…”
Section: Salmonella Typhimurium Deceives and Inhibits Dcsmentioning
confidence: 99%